Black American males in higher education research, programs and academe - Frierson, Henry T. 1944-; Wyche, James H.; Pearson, Willie, 1945- (Diversity in higher education ;, 2009)
Volume 7 is the second of two volumes in "Emerald's Diversity in Higher Education" series that specifically address the state of Black American males in higher education today. In this volume, the contributing authors, who as in Volume 6, come from a wide range of institutions and disciplines, present rich discussions related to reports on research and theoretical views pertaining to Black males in higher education. Further, presented in this volume are significant discussions of intervention programs within or associated with institutions of higher education as well as discourses on critical perspectives regarding the situation for Black males in academe. Many of the topics discussed in the two volumes have often been overlooked regarding the level of importance, but the gravity of the situation has become increasingly apparent and Volume 7 looks to contribute to content that address this crucial educational and societal issue surrounding the circumstances of Black American males and higher education.